ELECTRICAL DRIVE OF A MOBILE IRRADIATION INSTALLATION - ANDRIICHUK, VOLODIMIR; NAKONECHYI, MYROSLAV; FILIUK, YAROSLAV; KOSTYK, LIUBOV; KOZAK, IVAN (Herald of Khmelnytskyi National University. Technical sciences, 2023)
If the level of natural radiation is insufficient or in conditions of short daylight in greenhouses, additional irradiation of plants is used. The application of such optical electrical technologies is closely related to the problem of energy saving, therefore the question of using variable irradiation technology, to which this work is devoted, is relevant. The authors proposed an irradiation installation with rotational movement of the irradiator in the vertical and horizontal planes. As an irradiator, an LED light device lighting device DO73U-50-02 with a power of 50 W, manufactured by the Vatra Corporation OSP, was used. To rotate the irradiator in the horizontal plane, a 5IK60GN type gear motor with a gear ratio of 1:200 and a nominal motor rotation speed of 1300 rpm and a single-phase frequency converter with a power of 0.18 kW were used. A nema 23 stepper motor (23HS2430) and a DM556 driver were used to move the irradiator in the vertical plane. The paper proposes a mathematical model of the irradiation installation. The angles of relative rotation of links q1, q2 were used as the generalized coordinates of the support-rotation device as independent variables that fully determine the spatial orientation of the irradiator. They coincide with the angles of rotation of the irradiator in the corresponding planes and are on a certain scale with the angles of rotation of the shafts of the motors of the control system. An electric drive control system based on an Arduino Uno microcontroller, a frequency converter and a stepper motor driver is proposed.
Keywords: electric drive; variable irradiation; asynchronous motor; stepper motor; controller